Magnetic fabrics and microstructures of Paleoproterozoic intrusive bodies of Piedra Alta Terrane, Río de la Plata Craton, Uruguay: A reconnaissance study - Franceschinis, Pablo Reinaldo (2020)
Small to medium-sized intrusive bodies with ages between 2.1 and 2.0 Ga characterize Piedra Alta terrane and represent the final stabilization of Río de la Plata Craton. A reconnaissance study of petro- and magnetic fabrics based on microscopic observations, anisotropy of magnetic susceptibility and anhysteretic remanent magnetization, was carried out on 41 sites from 14 intrusive bodies, in order to obtain preliminary information on kinematics of their emplacement, degree of deformation, and regional stress regime during this magmatic event. The magnetic fabrics coupled with the microstructural analysis are interpreted as generally reflecting magma kinematics near solidus temperature, although few cases of tectonically modified fabrics at local levels have been interpreted. Field evidence and magnetic fabrics in most plutons show subvertical to high angle E-W to NE-SW trending foliations and subvertical lineations. These data suggest that plutons were probably intruded under a regional extensional to transtensional regime, which controlled the magma ascent and distribution of the intrusions. Lack of metamorphism and low to null deformation shown by the study plutons suggest a late-orogenic character for this magmatism, which has been associated with crustal stabilization after accretionary processes that led to the formation of Río de la Plata Craton in the Orosirian.